Can increasing dividends be a symptom of the financialization of the Polish economy? - Mieczysław Kowerski (e-Finanse: Financial Internet Quarterly, 2016)
Because operationally financialization may be detected by the increase of interest, dividends, or capital gains, the paper tries to answer the question as to whether the increased dividend payments observed in Poland can be a symptom of financialization. Analysis of basic tendencies of changes in propensities to pay dividends, values, structures and payout ratios of companies quoted in the years 1992-2014 on the Warsaw Stock Exchange tend towards the conclusion that the increase of dividend payouts at this time is not a sign of financialization of the economy. But because most of the phenomena connected with the dividend policy of the companies quoted on the WSE show similar tendencies to those of the developed equity markets, this may be a symptom of the financialization of the Polish economy in the future.
Keywords: G35; G38; G2; 330; dividends as the indicator of financialization; Warsaw Stock Exchange